Pemanfaatan Media Pembelajaran Berbasis Information And Communication Technology (Ict) Dan Fasilitas Belajar Terhadap Keaktifan Belajar Siswa Kelas X Akuntansi SMK BATIK 2 Surakarta Tahun Ajaran 2016/2017 - PRAVITA SARI, ROVIYANA; , Drs.Sami'an., M.M (2017)
The purpose of this research is to know:1) The media utilization learning-based on information and communication technology (ICT) to activeliness of student learning, 2) The facility of student learning towards student learning activity, 3) The utilization of learning media based on information and communication technology (ICT) and learning facilities on student learning activeness. The type of the research is quantitative associative. The population in this study is 83 students of class x of smk batik 2 surakarta, the 66 students were taken for sampling based on proportional random sampling method. The data collection technique using questionnaires that have been tested for the validity and reliability. Data analysis techniques used are t test, f test, coefficient of determination, multiple linear regression analysis, effective donation and relative donations. The conclusions of this research are: 1) The significant influence between utilization of learning media based on information and communication technology (ICT) on student learning activities based on t test obtained from the value of t arithmetic> t table is 4.184 >1.998 with probability significance value < 0.05 is 0,000 and effective contribution (se) of 31.6%. 2) There is significant influence between student learning facilities on student learning activity based on t test obtained value of t arithmetic > t table is 3.583 >1,998 with probability significance< 0.05 is 0.001 and effective contribution (se) is 26.1%. 3) There is a significant influence between the uzitilzation information and communication technology (ICT)and learning facilities on student learning activeness based on f test known f arithmetic <f table is 43,013 <3,143 with significance probability value < 0,05 is 0,000 with coefficient of determination (R2) equal to 57,7% whereas the remaining 42.3% is influenced by other variables of this study.